2009
DOI: 10.1007/s11205-009-9457-2
|View full text |Cite
|
Sign up to set email alerts
|

Personal Well-being in Urban China

Abstract: China, Personal wellbeing index, Subjective wellbeing,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
61
4
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 57 publications
19
61
4
4
Order By: Relevance
“…However, earlier studies on China have been at times narrow in terms of study population, for instance, focusing on some specific groups such as the elderly and urban residents (Knight and Gunatilaka, 2010;Smyth, Nielsen and Zhai, 2010; 1 Wu and Li (2013) examine the subjective consequence of rising income inequality amidst rapid economic growth in China. Based on the data from a nationally representative survey conducted in 2005, they show that, while personal income improves life satisfaction, local level income inequality has a negative effect on individuals' life satisfaction, but they did not look into the impact for different income groups.…”
Section: Introductionmentioning
confidence: 99%
“…However, earlier studies on China have been at times narrow in terms of study population, for instance, focusing on some specific groups such as the elderly and urban residents (Knight and Gunatilaka, 2010;Smyth, Nielsen and Zhai, 2010; 1 Wu and Li (2013) examine the subjective consequence of rising income inequality amidst rapid economic growth in China. Based on the data from a nationally representative survey conducted in 2005, they show that, while personal income improves life satisfaction, local level income inequality has a negative effect on individuals' life satisfaction, but they did not look into the impact for different income groups.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have found individual characteristics (such as gender, age, and education) (24)(25)(26), social support (26,27), social belonging (28), economic openness (29), and atmospheric pollution (30) to be associated with SWB among urban Chinese people, research focusing specifically on the neighborhood environment and SWB among elders in China has been limited. In fact, we could only find one such study (27), and this study did not examine individual, physical, and social environmental characteristics simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these studies focus on urban residents (Appleton and Song 2008;Smyth et al 2010;Wang and VanderWeele 2011;Jiang et al 2012;Huang et al 2015;Qian and Qian 2015;Akee et al 2015). But there have also been a few studies that examine the determinants of happiness for rural residents (Knight et al 2009) and rural-urban migrants (Gao and Smyth 2011;Knight and Gunatilaka 2010b;Nielsen et al 2010;Akay et al 2012).…”
Section: The Traditional Focus In Economics Has Been To Use Indicatormentioning
confidence: 99%